2018
DOI: 10.19082/6534
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effect of isolated probiotic bacteria from natural sources against intestinal Escherichia coli pathotypes

Abstract: BackgroundProbiotics are live microorganisms which are beneficial bacteria that are normal flora of the digestive system which, in determined amounts, show beneficial effects on host health, and can balance gastrointestinal microflora. Digestive tract diseases such as diarrhea are one of the major causes of child mortality in developing countries. Different pathotypes of Escherichia coli cause diarrhea that affects children, therefore reduction of these colonization strains in humans or animals can decline gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…In a study to evaluate the potential of Zimbabwean commercial probiotic products and strains of L. plantarum as prophylaxis and therapy against diarrhea caused by E. coli in children, it was confirmed that the LAB grossly inhibited diarrhoeagenic clinical E. coli strains compared to L. rhamnosus LGG strain and probiotic products which were widely used for prophylaxis and therapeutic purposes (Chingwaru & Vidmar, 2017). This finding was further confirmed by other independent studies (Karimi, Rashidian, Birjandi, & Mahmoodnia, 2018; Yang et al, 2014).…”
Section: Resultssupporting
confidence: 85%
“…In a study to evaluate the potential of Zimbabwean commercial probiotic products and strains of L. plantarum as prophylaxis and therapy against diarrhea caused by E. coli in children, it was confirmed that the LAB grossly inhibited diarrhoeagenic clinical E. coli strains compared to L. rhamnosus LGG strain and probiotic products which were widely used for prophylaxis and therapeutic purposes (Chingwaru & Vidmar, 2017). This finding was further confirmed by other independent studies (Karimi, Rashidian, Birjandi, & Mahmoodnia, 2018; Yang et al, 2014).…”
Section: Resultssupporting
confidence: 85%
“…Thus, it is crucial that an organism is able to inhibit the growth of pathogenic organisms without producing any metabolites that could be harmful to the host before it is considered as a probiotic. It has been reported recently that harsh living conditions accompanied with reduced physical activity, stress, inadequate nutrition and unhealthy lifestyle have increased human susceptibility to infectious diseases whereas, the incessant use of synthetic antimicrobial agent such as antibiotics has increased the resistance of infectious agents ( Karami et al., 2018 ), creating serious health problems and future medicinal concerns thus making natural antimicrobials such as probiotics very essential. The ability of P. acidilactici to inhibit different pathogens in this study is probably due to the production of lactic acid and other organic acids or metabolites that are able to increase the acidic condition of the medium thus causing damage to the membrane proteins making it unbearable for pathogens to survive.…”
Section: Discussionmentioning
confidence: 99%
“…delbrueckii and different pools of Lactobacillus (Poppi et al, 2015), L. plantarum, L. fermentum and B. bidifum PTCC 1644 (Hesari et al, 2017), L. lactis, L. casei and L. reuteri (de Marco et al, 2018), L. plantarum, L. gasseri (Karimi et al, 2018) supernatants against E. coli was studied. Karimi et al (2018) have detected the inhibitory effect of the supernatants of two probiotic lactobacilli (L. plantarum and L. gasseri) on the growth of four pathotypes of E. coli (enterotoxigenic, enteroaggregate, enteroinvasive and enteropathogenic) using two methods: disk diffusion and well diffusion agar methods. Poppi and co-authors reported that the supernatant from L. reuteti exhibited bactericidal activity toward pathogenic E. coli strain O157:H7.…”
Section: Discussionmentioning
confidence: 99%